2020
DOI: 10.7717/peerj.8600
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA polymorphisms on 8q24 are associated with the prognosis of gastric cancer in a Chinese population

Abstract: Background Gastric cancer (GC) remains the third leading cause of cancer death in China. Although genome-wide association studies have identified the association between several single nucleotide polymorphisms (SNPs) on 8q24 and the risk of GC, the role of these SNPs in the prognosis of GC in Chinese populations has not yet been fully evaluated. Therefore, this study was conducted to explore the association between long non-coding RNA (lncRNA) polymorphisms on 8q24 and the prognosis of GC. Methods We genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Most of the studies on CASC8 have focused on its polymorphism. CASC8 rs10505477 polymorphism was found to be greatly associated with gastrointestinal toxicity in small cell lung cancer (SCLC) and could serve as a possible risk marker for diagnosing lung cancer and could be used to forecast the response and toxicity of platinum-based treatment in lung cancer patients (Hu et al, 2016;Zhang et al, 2020). The rs10505477 is located in the intron of CASC8 which overlaps with the POU5F1B (POU class 5 homeobox 1 pseudogene 1) gene.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the studies on CASC8 have focused on its polymorphism. CASC8 rs10505477 polymorphism was found to be greatly associated with gastrointestinal toxicity in small cell lung cancer (SCLC) and could serve as a possible risk marker for diagnosing lung cancer and could be used to forecast the response and toxicity of platinum-based treatment in lung cancer patients (Hu et al, 2016;Zhang et al, 2020). The rs10505477 is located in the intron of CASC8 which overlaps with the POU5F1B (POU class 5 homeobox 1 pseudogene 1) gene.…”
Section: Discussionmentioning
confidence: 99%
“…The rs10505477 is located in the intron of CASC8 which overlaps with the POU5F1B (POU class 5 homeobox 1 pseudogene 1) gene. A study on a Chinese population found that rs10505477 GA heterozygote in CASC8 was associated with a significantly lower survival rate in gastric cancer (Zhang et al, 2020). A meta-analysis for CASC8 in cancer showed that, compared with the individuals carrying the rs10505477 TT genotype, those with the TC or CC genotype had a decreased risk of cancer, whereas for rs7837328, the GA and AA genotypes were associated with increased risks of cancer as compared with the GG genotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations